2020
DOI: 10.3390/microorganisms8091349
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Wine Aromatic Amino Acid Catabolites by Using Torulaspora delbrueckii in Sequentially Inoculated Fermentations or Saccharomyces cerevisiae Alone

Abstract: Yeasts are the key microorganisms that transform grape juice into wine, and nitrogen is an essential nutrient able to affect yeast cell growth, fermentation kinetics and wine quality. In this work, we focused on the intra- and extracellular metabolomic changes of three aromatic amino acids (tryptophan, tyrosine, and phenylalanine) during alcoholic fermentation of two grape musts by two Saccharomyces cerevisiae strains and the sequential inoculation of Torulaspora delbrueckii with Saccharomyces cerevisiae. An U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…We observed dynamic changes between TOL and its sulfonated adduct, TOL-SO 3 H, during wine storage, an event associated with wine aging and promoted by small amounts of oxygen [ 15 , 16 ]. Recently, small amounts of TOL-SO 3 H were detected during laboratory-scale fermentation of a Chardonnay must with a yeast strain that produced high concentrations of TOL and SO 2 , indicating that sulfonation of TOL can also occur in anaerobic conditions [ 17 ]. Similarly, in our Chardonnay study, trace amounts of TOL-SO 3 H were found just after alcoholic fermentation, but only in the wines made with the highest TOL producer, AWRI2940.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed dynamic changes between TOL and its sulfonated adduct, TOL-SO 3 H, during wine storage, an event associated with wine aging and promoted by small amounts of oxygen [ 15 , 16 ]. Recently, small amounts of TOL-SO 3 H were detected during laboratory-scale fermentation of a Chardonnay must with a yeast strain that produced high concentrations of TOL and SO 2 , indicating that sulfonation of TOL can also occur in anaerobic conditions [ 17 ]. Similarly, in our Chardonnay study, trace amounts of TOL-SO 3 H were found just after alcoholic fermentation, but only in the wines made with the highest TOL producer, AWRI2940.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction is favoured by the presence of small amounts of oxygen in wine [ 15 ], and the equilibrium towards the formation of TOL-SO 3 H from TOL seems to be increased by bottle aging, particularly for white wines [ 16 ]. Although the effect of TOL-SO 3 H on the taste and mouthfeel properties of fermented beverages remains unclear, it has recently been linked with bitterness [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, their amount in the wine is determined by the number of amino acids found in grapes, such as Tyr and Trp. Moreover, N-Tyr-EE plays an active role as a Trp synthase inhibitor in regulating Trp synthesis and metabolism in yeast [48]. The Ila aglycon of hydrolyzed Ila-Glu can react with SO2 and produce the sulfonated indole Ila-SO3H.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, Ruiz et al [ 54 ] concluded that during wine fermentation T. delbrueckii may influence the response of S. cerevisiae to nitrogen availability, thereby affecting the course of the fermentation process. Regarding access to nitrogen, Álvarez-Fernández et al [ 55 ] suggested that T. delbrueckii initiates nitrogen utilization by activating metabolic pathways other than those preferred by S. cerevisiae , resulting in the consumption of the available nitrogen sources in a different order (e.g., first ammonium sulphate and then amino acids) compared to its competitor. This supports the co-existence and the prolonged activity of both populations in mixed fermentations.…”
Section: Ns–sc Interactionsmentioning
confidence: 99%